Union Statistics for for fifty years - South Africa. Bureau of Census and Statistics (Bureau of Census and Statistics, 1960)
This publication provides a statistical resume of the Union of South Africa's growth and development during the fifty year period from 1910-1960.
Uniestatistieke oor vyftig jaar
Keywords: South Africa--Population--Census